Determinação da potencialidade hidrogeológica em uma área no município de Araçariguama-SP - De Mario, André Felipe Gonçalves [UNESP]; Dourado, João Carlos [UNESP] (My University, 2013)
This work discuss a methodology for evaluating the hydrogeological potential in the area of Residential Condominium Villa Verde, in Araçariguama - SP municipality, based on the analysis and the intersection of historical information, bibliographic references, remote sensing and geology. There are two boreholes in Villa Verde, the first one drilled during the construction of Villa Verde and the second one did in 2002 when the first borehole could not support the demand for water in Villa Verde any more. The borehole was perforated after a geological and geophysical study in the area to determine it's the best location, however it did not produce water. Geologically the studied area is located over the São Roque granitoid and the metasediments of Serra do Itaberaba Formation (shales). Because of this geological context the aquifer model considered is fractured, what made important emphasize the discontinuity in the structural characterization of bedrock. This study had a practical focus that aimed the definition of potential structures that could be able to have a fractured aquifer, indicating the areas for a detailed prospective study, which can be direct (drilling) or indirect (ground geophysics).
Determination of potential in a hydrogeological area in city of Araçariguama-SP
Keywords: Araçariguama; Hydrogeology